Graphene light propulsion: experimental investigation, modeling, and potential application for deorbiting in low earth orbit - Haidong Zhu; Feng Sun; Tingwei Fu; Xiang Liu; Guoping Cai (Advances in Space Research, 2026)

Epilepsy associated with unusual white matter hyperintensity growth in a cerebral developmental venous anomaly - Lingjia Xu; Guoping Fu; Yang Zhou (Acta Neurologica Belgica, 2026)

Combined aperture widening and strong polarization in Li+-exchanged mordenite for efficient direct air capture of CO2 - Zhifu Liu; Guanghui Shi; Shuzhuang Sun; Yong Wang; Jingyue Shang; Songbai Hu; Wenkang Deng; Chuhan Fu; Chenghao Liu; Xiao Wang; Tao Qi; Guoping Hu (Chemical Engineering Journal, 2026)

BarleyOmics: A comprehensive multi-omics database of barley - Junheng Zhao; Shanggeng Xie; Chenyang Zhang; Zengjie Hu; Xiangqian Lu; Nannan Zheng; Yujie Fu; Jie Yao; Ping Zhou; Danyin Huang; Zhizhong Zhang; Mengdi Li; et al. (Molecular Plant, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

m6A-Mediated Upregulation of lncRNA CHASERR Promotes the Progression of Glioma by Modulating the miR-6893-3p/TRIM14 Axis - Xingwei Wu; Minjie Fu; Chang Ge; Hanyu Zhou; Haoyu Huang; Min Zhong; Mengying Zhang; Hao Xu; Guoping Zhu; Wei Hua; Kun Lv; Hui Yang (Molecular Neurobiology, 2024)

CO2 capture using low silica X zeolite synthesized from low-grade coal gangue via a two-step activation method - Chenghao Liu; Fu Rao; Yalou Guo; Zhe Lu; Wenkang Deng; Guobiao Li; Hui Zhang; Tao Qi; Guoping Hu (Journal of Environmental Chemical Engineering, 2024)

Ocean-Mixer: A Deep Learning Approach for Multi-Step Prediction of Ocean Remote Sensing Data - Sai Wang; Guoping Fu; Yongduo Song; Jing Wen; Tuanqi Guo; Hongjin Zhang; Tuantuan Wang (Journal of Marine Science and Engineering, 2024)
The development of intelligent oceans requires exploration and an understanding of the various characteristics of the oceans. The emerging Internet of Underwater Things (IoUT) is an extension of the Internet of Things (IoT) to underwater environments, and the ability of IoUT to be combined with deep learning technologies is a powerful technology for realizing intelligent oceans. The underwater acoustic (UWA) communication network is essential to IoUT. The thermocline with drastic temperature and density variations can significantly limit the connectivity and communication performance between IoUT nodes. To more accurately capture the complexity and variability of ocean remote sensing data, we first sample and analyze ocean remote sensing datasets and provide sufficient evidence to validate the temporal redundancy properties of the data. We propose an innovative deep learning approach called Ocean-Mixer. This approach consists of three modules: an embedding module, a mixer module, and a prediction module. The embedding module first processes the location and attribute information of the ocean water and then passes it to the subsequent modules. In the mixing module, we apply a temporal decomposition strategy to eliminate redundant information and capture temporal and channel features through a self-attention mechanism and a multilayer perceptron (MLP). The prediction module ultimately discerns and integrates the temporal and channel relationships and interactions among various ocean features, ensuring precise forecasting. Numerous experiments on ocean temperature and salinity datasets show that Mixer-Ocean performs well in improving the accuracy of time series prediction. Mixer-Ocean is designed to support multi-step prediction and capture the changes in the ocean environment over a long period, thus facilitating efficient management and timely decision-making for innovative ocean-oriented applications, which has far-reaching significance for developing and conserving marine resources.

Distinct resting-state functional connectivity patterns of Anterior Insula affected by smoking in mild cognitive impairment - Tianyi Zhang; Qingze Zeng; Kaicheng Li; Xiaocao Liu; Yanv Fu; Tiantian Qiu; Peiyu Huang; Xiao Luo; Zhirong Liu; Guoping Peng (Brain Imaging and Behavior, 2023)
Smoking is a modifiable risk factor for Alzheimer’s disease (AD). The insula plays a vital role in both smoking and cognition. However, the smoking effects on insula-related networks in cognitively normal controls (CN) and mild cognitive impairment (MCI) patients remain unknown. We identified 129 CN (85 non-smokers and 44 smokers) and 83 MCI (54 non-smokers and 29 smokers). Each underwent neuropsychological assessment and MRI (structural and resting-state functional). Seed-based functional analyses in the anterior and posterior insula were performed to calculate the functional connectivity (FC) with voxels in the whole brain. Mixed-effect analyses were performed to explore the interactive effects on smoking and cognitive status. Associations between FC and neuropsychological scales were assessed. Mixed-effect analyses revealed the FC differences between the right anterior insula (RAI) with the left middle temporal gyrus (LMTG) and that with the right inferior parietal lobule (RIPL) ( p < 0.01, cluster level < 0.05, two-tailed, gaussian random field correction). The FC of RAI in both LMTG and RIPL sees a significant decrease in MCI smokers ( p < 0.01). Smoking affects insula FC differently between MCI and CN, and could decrease the insula FC in MCI patients. Our study provides evidence of neural mechanisms between smoking and AD.

Exosomes from human urine-derived stem cells carry NRF1 to alleviate bladder fibrosis via regulating miR-301b-3p/TGFβR1 pathway - Junwei Wu; Xinxin Wang; Guoping Fu; Yiyuan Feng; Yan Wang; Guoxian Zhang; Yudong Wu; Lirong Zhang; Hongyu Meng; Jianguo Wen; Bing Zhang; Qingwei Wang (Molecular and Cellular Biochemistry, 2023)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Genetic and clinical determinants of mizoribine pharmacokinetics in renal transplant recipients - Rui Dai; Jingjie Li; Jingjing Wu; Qian Fu; Jiajia Yan; Guoping Zhong; Changxi Wang; Xiao Chen; Pan Chen (European Journal of Clinical Pharmacology, 2021)

Characterization of a novel victorivirus isolated from the phytopathogenic fungus Botryosphaeria dothidea - Mengmeng Yang; Lifeng Zhai; Feng Xiao; Yashuang Guo; Min Fu; Ni Hong; Guoping Wang (Archives of Virology, 2019)

ZIKA virus isolated from mosquitoes: a field and laboratory investigation in China, 2016 - Shihong Fu; Song Song; Hong Liu; Yuanyuan Li; Xiaolong Li; Xiaoyan Gao; Ziqian Xu; Guoping Liu; Dingming Wang; Zhenzao Tian; Jingzhu Zhou; Ying He; et al. (Science China Life Sciences, 2017)

Characterization of a novel botybirnavirus isolated from a phytopathogenic Alternaria fungus - Jun Xiang; Min Fu; Ni Hong; Lifeng Zhai; Feng Xiao; Guoping Wang (Archives of Virology, 2017)

Genotypic-dependent effects of N fertilizer, glutathione, silicon, zinc, and selenium on proteomic profiles, amino acid contents, and quality of rice genotypes with contrasting grain Cd accumulation - Fangbin Cao; Manman Fu; Runfeng Wang; Wangda Cheng; Guoping Zhang; Feibo Wu (Functional & Integrative Genomics, 2017)

Influence of reducing conditions on the release of antimony and arsenic from a tailings sediment - Zhiping Fu; Guoping Zhang; Haixia Li; Jingjing Chen; Fengjuan Liu; Qiong Wu (Journal of Soils and Sediments, 2016)

Assessment of the Altitudinal Atmospheric Metal(loid) Deposition in a Mountainous City by Mosses - Haixia Li; Guoping Zhang; Hong Liu; Ling Li; Zhiping Fu; Xiaoxue Ouyang; Jingjing Chen; Jian Hu (Bulletin of Environmental Contamination and Toxicology, 2015)

Interaction between Pazufloxacin and DNA Mediated by Copper(II) Ions - Guoliang Zhang; Xuchun Fu; Qingwang Liu; Guoping Wang (Journal of Fluorescence, 2008)

Microbial Metabolism of Quinoline by Comamonas sp. - Mingchao Cui; Fanzhong Chen; Jiamo Fu; Guoying Sheng; Guoping Sun (World Journal of Microbiology and Biotechnology, 2004)